2021
DOI: 10.1177/03000605211032493
|View full text |Cite
|
Sign up to set email alerts
|

Clinical challenges and management of primary renal epithelioid angiomyolipoma of duplex kidney with paraneoplastic syndrome

Abstract: Giant renal epithelioid angiomyolipoma of a duplex kidney has rarely been reported, especially in patients with paraneoplastic syndrome. The present report describes a 33-year-old man of Miao nationality who presented with a 6-month history of intermittent dull pain in the left upper abdomen that occurred after eating. Ultrasonography, intravenous pyelography, and computed tomography revealed a mass lesion localized in the left kidney and connected to the left renal artery. Radical nephrectomy was successfully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Some patients, depending on the location and size of the tumors, may also have clinical symptoms such as fatigue, fever, low back pain, abdominal pain, hematuria, bleeding, dysuria, and renal dysfunction. Recently, Benincasa et al 4 reported a case of spontaneous renal rupture caused by PEComa, and although this is relatively rare in clinical practice, it should receive attention as the tumor is also known to cause paraneoplastic syndromes such as a high erythrocyte sedimentation rate, elevated platelet count, and hormonal and immune system abnormalities 5 …”
Section: Epidemiological Characteristics Of Renal Epithelioid Angiomy...mentioning
confidence: 99%
See 1 more Smart Citation
“…Some patients, depending on the location and size of the tumors, may also have clinical symptoms such as fatigue, fever, low back pain, abdominal pain, hematuria, bleeding, dysuria, and renal dysfunction. Recently, Benincasa et al 4 reported a case of spontaneous renal rupture caused by PEComa, and although this is relatively rare in clinical practice, it should receive attention as the tumor is also known to cause paraneoplastic syndromes such as a high erythrocyte sedimentation rate, elevated platelet count, and hormonal and immune system abnormalities 5 …”
Section: Epidemiological Characteristics Of Renal Epithelioid Angiomy...mentioning
confidence: 99%
“…reported a case of spontaneous renal rupture caused by PEComa, and although this is relatively rare in clinical practice, it should receive attention as the tumor is also known to cause paraneoplastic syndromes such as a high erythrocyte sedimentation rate, elevated platelet count, and hormonal and immune system abnormalities. 5 3 | ETIOLOGY AND PATHOGENESIS OF RENAL EPITHELIOID ANGIOMYOLIPOMA Tuberous sclerosis complex (TSC) is an autosomal dominant disorder characterized by hamartomas of the brain, heart, skin, lungs, and kidneys. 6 Studies have shown that a close relationship between renal AML and TSC exists.…”
mentioning
confidence: 99%